Pengaruh Pendidikan dan Upah Minimum Terhadap Kemiskinan di Provinsi Aceh - Meutia Balqis; Nurlathifatul Qalbiyah Sinaga; Asnidar Asnidar; Nurlaila Hanum; Puti Andiny; Safuridar Safuridar (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This research aims to determine the effect of education and minimum wages on poverty in Aceh province. This research uses secondary data, namely those obtained from the Central Statistics Agency of Aceh Province. The method used in this research is a quantitative method using multiple linear analysis. The research results show that partially the education variable has a negative and significant influence on poverty in Aceh province, while the Minimum Wage variable has a positive and insignificant influence on poverty in Aceh Province. Simultaneously, the variables education and minimum wage together have a significant effect on poverty in Aceh Province.